Effect of Mycotoxin-Containing Diets on Epigenetic Modifications of Mouse Oocytes by Fluorescence Microscopy Analysis. (9th May 2014) - Zhu, Cheng-Cheng; Hou, Yan-Jun; Han, Jun; Liu, Hong-Lin; Cui, Xiang-Shun; Kim, Nam-Hyung; Sun, Shao-Chen
Abstract: Mycotoxins, such as aflatoxin (AF), fumonisin B1, zearalenone (ZEA), and deoxynivalenol (DON), are commonly found in many food commodities. Mycotoxins have been shown to increase DNA methylation levels in a human intestinal cell line. We previously showed that the developmental competence of oocytes was affected in mice that had been fed a mycotoxin-containing diet. In this study, we explored possible mechanisms of low mouse oocyte developmental competence after mycotoxin treatment in an epigenetic modification perspective. Mycotoxin-contaminated maize (DON at 3, 875 μ g/kg, ZEA at 1, 897 μ g/kg, and AF at 806 μ g/kg) was included in diets at three different doses (mass percentage: 0, 15, and 30%) and fed to mice for 4 weeks. The fluorescence intensity analysis showed that the general DNA methylation levels increased in oocytes from high dose mycotoxin-fed mice. Mouse oocyte histone methylation was also altered. H3K9me3 and H4K20me3 level increased in oocytes from mycotoxin-fed mice, whereas H3K27me3 and H4K20me2 level decreased in oocytes from mycotoxin-fed mice. Thus, our results indicate that naturally occurring mycotoxins have effects on epigenetic modifications in mouse oocytes, which may be one of the reasons for reduced oocyte developmental competence.